Dinamika Komunikasi Humas Kementerian Komunikasi Dan Informatika Dalam Memberantas Hoax Dan Ujaran Kebencian Di Media Sosial - Olivia, Helen; Leonita, Winda (FISIP IBI-K57 Prodi Komunikasi, 2020)
This research discusses how the dynamics of public relations communication of the Ministry of Communication and informatics in eradicating hoaxes and speech on social media. The research objective was to determine the dynamics of communication, steps and obstacles in eradicating hoaxes and hate speech. This research uses Computer Mediated Communication (CMC) theory and action theory. The paradigm used is constructivism with a qualitative research approach. The method used is a case study. Research subjects in the study consisted of key informants and informants. Data collection techniques using interviews, observation and documentation. The results of this study indicate that the dynamics of communication are carried out through face-to-face (direct) communication and media (indirect) communication. The steps taken in eradicating hoaxes and hate speech are by providing direction to the public through open seminars and on their way being hampered by time and location constraints. Obstacles found in the process of blocking websites or social media, Kominfo cannot directly block them but must wait for recommendations from other parties that are in accordance with their respective sectors